Antimicrobial and protective effects of non-thermal plasma treatments on the performance of a resinous liner - Nagay, Bruna Egumi; Bitencourt, Sandro Basso [UNESP]; Commar, Betina Chiarelo [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; dos Santos, Daniela Micheline [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Goiato, Marcelo Coelho [UNESP]; Del Bel Cury, Altair Antoninha; Ricomini-Filho, Antônio Pedro; Barão, Valentim Adelino Ricardo (Elsevier, 2020)
Objective: Overcoming substantial shortcomings of soft liners as physico-chemical changes and liner-biofilm-related infections remains a challenge in the rehabilitation treatment. In this study, protective non-thermal plasma (NTP) treatments were developed on the soft liner surface to improve its surface and physico-chemical properties and to reduce fungal colonization after biofilm inhibition challenge. Methods: Resinous liner specimens (Coe-Soft) were prepared and distributed in 3 groups according to the surface treatments: (1) untreated (control); (2) treated with sulfur hexafluoride-based NTP (SF6); and (3) treated with hexamethyldisiloxane-based NTP (HMDSO). To test the NTP stability and their protective and antimicrobial effect on the liner surface over time, the morphology, chemical composition, roughness, water contact angle, shore A hardness, sorption and solubility were evaluated before and after the specimens were exposed to dual-species biofilm of Candida albicans and Streptococcus oralis for 14 days. Colony forming units and biofilm structure were assessed. Data were submitted to ANOVA and Tukey tests (α = 0.05). Results: Both treatments modified the surface morphology, increased hydrophobicity and roughness of the liner, and were effective to reduce C. albicans adhesion without affecting the commensal health-associated S. oralis. HMDSO presented chemical stability and lower hardness in both periods, whereas SF6 exhibited higher initial hardness than control and the highest sorption; contrarily, similar solubility was noted for all groups. Conclusion: HMDSO-based film showed improved physico-chemical properties and inhibited C. albicans biofilm. Thus, it has potential for use to control candida-related stomatitis and improve liner's stability even after being exposed to biofilm inhibition challenge.
Keywords: Biofilms; Denture liners; Plasma gases; Surface properties